The Effect of CR and EPS on Stock Prices Listed on the Kompas100 Index. - Amelia, Dwi; Meirisa , Faradila (Sean Institute, 2025)
This study analyzes the effect of Current Ratio (CR) and Earning Per Share on Stock Price in Kompas100 Index companies for the period 2019-2023 Using hypothesis testing, the research sample consisted of 92 companies. The results showed that CR has no effect and is significant and EPS has a negative and significant effect on Stock Price. Simultaneously the two variables have a significant influence with an Adjusted R² of 5.5%, which indicates that other factors also affect the Stock Price.